2015
DOI: 10.1128/mcb.00549-15
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Regulates Transient Receptor Potential Vanilloid 2 via Extracellular Signal-Regulated Kinase Signaling To Enhance Neurite Outgrowth in Developing Neurons

Abstract: Neurite outgrowth is key to the formation of functional circuits during neuronal development. Neurotrophins, including nerve growth factor (NGF), increase neurite outgrowth in part by altering the function and expression of Ca 2؉ -permeable cation channels. Here we report that transient receptor potential vanilloid 2 (TRPV2) is an intracellular Ca 2؉ -permeable TRPV channel upregulated by NGF via the mitogen-activated protein kinase (MAPK) signaling pathway to augment neurite outgrowth. TRPV2 colocalized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 67 publications
5
54
0
Order By: Relevance
“…Furthermore, heat sensitivity appears not to be conserved in human TRPV2 [83]. There is evidence that TRPV2 plays a role in neurite outgrowth, particularly in response to mechanical stretch of neurons [81] or nerve growth factor stimulation [84]. Whether this has implications for nerve regeneration in the skin has yet to be explored.…”
Section: Contributions Of Trp Channels To Skin Biology and Pathophmentioning
confidence: 99%
“…Furthermore, heat sensitivity appears not to be conserved in human TRPV2 [83]. There is evidence that TRPV2 plays a role in neurite outgrowth, particularly in response to mechanical stretch of neurons [81] or nerve growth factor stimulation [84]. Whether this has implications for nerve regeneration in the skin has yet to be explored.…”
Section: Contributions Of Trp Channels To Skin Biology and Pathophmentioning
confidence: 99%
“…Ca 2 þ imaging experiments were performed with membrane-permeable Fluo4 (Fluo4-AM, Life Technologies) as described previously 14 . In short, F11 cells were co-transfected with the TRPV2 protein and red fluorescent protein (RFP), which identified transfected cells.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that post-translational modifications, lipid-protein interactions and protein-protein interactions may regulate the function of these channels 2 . Specifically, phosphatidylinositol 4,5-bisphosphate (PIP 2 ) levels in the membrane may modulate TRPV2 activity 17 , and direct phosphorylation of TRPV2 by extracellular-signal-regulated kinases has been shown to regulate TRPV2 expression and activity 14 . A detailed structural analysis of TRPV2 may provide deeper insight into the cellular function of TRPV2, which has been elusive since its discovery 7,12,18 .…”
mentioning
confidence: 99%
“…In addition, Ca 2+ influx via NMDA receptors regulates Rho‐GTPase activity through Lim1/ IQGAP1/Cdc42 complexes, which facilitate actin poly‐merization in cultured cerebellar granule cells (2830). Moreover, TRPV2 phosphorylation in the early endosome is regulated by the nerve growth factor (NGF)/ tropomyosin receptor kinase A (TrkA) signaling path‐way, and its activation induces Ca 2+ release from endo‐somes to enhance axonal outgrowth (31). As described above, [Ca 2+ ] i transients induced by extracellular factors are important for growth cone motility, axonal out‐growth, and circuit formation in the spinal cord; however, it remains unknown whether Ca 2+ transients triggered by mechanically evoked TRPV2 activation contribute to growth cone motility or axonal outgrowth.…”
mentioning
confidence: 99%